Dictatorship and revolution: Socio-political reconstructions of collective memory in post-authoritarian Portugal - Loff, Manuel (2014)
This article inserts itself into larger discussions regarding post-dictatorship memory politics in Portugaland comparative studies of similar histories of violence in Europe, particularly examinations of National-Socialism, Nazism and the Holocaust, as well as comparative studies of twentieth-century fascist dictatorships in the Iberian peninsula. In spite of the revolutionary, radical nature of the Portuguese democratisation process, studies conducted during the last four decades on the social and political (re)constructions of memory regarding the Portuguese dictatorship (1926-1974) have demonstrated that state policies regarding the past have depicted the dictatorship as one that is very similar to events in countries where the process of democratic transition was actually quite different from that of Portugal. Right-wing groups and those who self-describe as victims of processes of decolonisation that occurred between 1974 and 1975 have established a pattern of public debate that leaves no room for discussing the dictatorship without also referring to the 1974-1975 Revolution. This mode of debate seems to suggest that these two periods of history are indicative of a global regime phenomenon and that both the processes ofdecolonisation and revolution affected Portuguese society in similar ways. This paper attempts to complicate these narratives in order to question the democratic forms that emerged after the Revolution and to compare it to Salazars dictatorial regime.